Factors associated with mobile phone usage to access maternal and child healthcare among women of urban slums in Dhaka, Bangladesh: a cross-sectional study. Issue 4 (9th April 2021) - Mistry, Sabuj Kanti; Akter, Fahmida; Yadav, Uday Narayan; Hossain, Md Belal; Sichel, Amarynth; Labrique, Alain B; Storisteanu, Daniel M L
Abstract : Introduction: With the acute shortage of human resources and infrastructure, mobile phones can be a critical tool for accessing health services and strengthening health systems in Bangladesh. Yet, there is a scarcity of evidence on the use of mobile phones in this context for accessing health services. In this study, we sought to explore the current use of mobile phones for accessing maternal and child healthcare and its determinants among recently delivered women in urban slums of Bangladesh. Methods: The data were collected through interviewing 800 recently delivered women from eight slums of Dhaka city of Bangladesh during May and June 2018. The study followed a cross-sectional design and a two-stage cluster random sampling procedure was followed. A pretested structured questionnaire was employed to collect information. Chi square tests were performed for descriptive analyses and a multilevel binary logistic regression model was executed to explore the determinants of mobile phone usage for accessing maternal and childcare among the participants. Results: Overall, 73.8% of study participants used mobile phones for accessing maternal and child healthcare. After adjusting for potential confounders, participants' age, husband's occupation, sex of household head, women's ownership of mobile phones and household wealth status were found to be significantly associated with higher odds of using mobile phones to access maternal and child healthcare. Conclusion: The study highlighted the possibility of implementing large-scale mobile health (mHealth) interventions in slum settlements for accessing maternal and child healthcare and is a sustainable mitigation strategy for the acute health worker crisis in Bangladesh. The findings of this study are particularly crucial for policymakers and practitioners while they revise the health policy to incorporate mHealth interventions as highlighted in the recently initiated Digital Health Strategy of Bangladesh.